The Role of Mangrove Forests in Promoting Tourism and Conversation in Dumai City - Febrina Wetri; Abdillah Nuryasin; Yusriza Yusrizal; Putra Sony Adiya; Srihandayani Susy (E3S Web of Conferences)
The dimishing green spaces and the status of Dumai City as one of the municipalities with the largest forest areas in Indonesia have prompted the need to investigate and assess the potential of mangrove forests as part of the tourism landscape in Dumai City. Dumai City Forest Tourism is part of the Sungai Dumai Nature Park (Taman Wisata Alam Sungai Dumai), This tourism forest includes mangrove forest areas, commonly known as Bandar Bakau. Using a semi-literature review and SWOT analysis, this research assesses the ecological and community impacts of integrating Bandar Bakau mangroves into tourism. Results show that Bandar Bakau is historically a mangrove forest conservation area that protects the coastline near the mouth of the Dumai River. Within this mangrove forest, there are several species of flora and fauna that need preservation, as some are on the brink of extinction. Collaboration from all parties is essential to protect this mangrove forest from damage. This research aims to evaluate the potential of the mangrove forest area in Dumai City as a tourism area and to assess its impact on the lives of the surrounding community. This research provides a model for integrating conservation with tourism, aligning environmental protection with socio-economic benefits.